Structure of the vacuum in deformed supersymmetric chiral models - Fernández, Pablo Sebastián (2008)
We analyze the vacuum structure of Ɲ = 1/2 chiral supersymmetric theories in deformed superspace. In particular we study O'Raifeartaigh models with C-deformed superpotentials and canonical and non-canonical deformed Kähler potentials. We find conditions under which the vacuum configurations are affected by the deformations.